Pengaruh Brand Ambassador, Layanan Cash on Delivery, Kualitas Pelayanan, Kualitas Produk dan Online Customer Review Terhadap Keputusan Pembelian E-Commerce Shopee Pada Mahasiswa PMM3 UNP - Ahmad Adi Wantoro (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to determine the influence of Brand Ambassador, Cash on Delivery service, service quality, product quality, and Online Customer Reviews on purchasing decisions of students of the Independent Student Exchange Program 3 (PMM3) Padang State University who use Shopee e-commerce. The study used a quantitative approach with an accidental sampling technique on 60 respondents. Data analysis was conducted using multiple linear regression to test the influence partially and simultaneously. The results showed that partially only Online Customer Reviews had a significant influence on purchasing decisions, while the variables Brand Ambassador, Cash on Delivery service, service quality and product quality did not have a significant influence. However, simultaneously all five variables had a significant influence on purchasing decisions. This indicates that internal factors, especially customer reviews, are considered more honest, relevant, and helpful in minimizing purchasing risks, especially considering students' limited income.